Tasavvuf Edebiyatında İçki Kavramına Giriş ve Yunus Emre Örneği - Saraç, M. A. Yekta (İlim Yayma Cemiyeti, 2000)
lt is necessary to redefine some of the important classical terms and concepts in order to understand the Divan poetry in a more detailed way. One of them is the concept of "wine". This work concerns analysis and interpretation of this concept within its all associations and it also shows how the changes in its meaning has took place through the passage of time. The results gathered from texts have been compared to the similar elements in the Divan of Yunus Emre.
Introduction to the Concept of Wine in Sufi Literature and lts Representation by Yunus Emre
Keywords: Divan Poetry; Poetry; Sufi Literature; Wine; Yunus Emre